Understanding Energy Poverty through the Perspective of Trade Openness and Foreign Direct Investment: An Empirical Case for Selected Latin American Countries - Cengiz, Orhan; Manga, Müge (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Energy poverty is still one of the critical problems for many countries. For this purpose, we try to assess whether trade openness and foreign direct investment are associated with energy poverty for the panel sample of Belize, Bolivia, Honduras, Mexico, Nicaragua, Panama, and Peru, spanning the period 1992-2020. The Panel Vector Auto Regression (PVAR) estimation results indicate that economic growth, trade openness, and foreign direct investment inflow reduce energy poverty by increasing access to electricity in these countries. Further, Panel VAR Granger causality findings show feedback causality linkage between energy poverty and trade openness, energy poverty and foreign direct investment inflow, economic growth and trade openness, and economic growth and foreign direct investment inflow. Moreover, the outcomes indicate that a bidirectional causality exists from economic growth to energy poverty and from trade openness to foreign direct investment inflow.